Psychological services for people with stroke: compliance with the UK National Clinical Guidelines - Bowen, Audrey; Knapp, Peter; Hoffman, Alex; Lowe, Derek (Clinical rehabilitation, 2005)
Background: The UK National Clinical Guidelines for Stroke (2000) include recommendations on psychological services. The third National Sentinel Audit of Stroke was completed in 2001-2002. Objectives: To examine the extent to which UK stroke services complied with the national guidelines. Design: Use of three retrospective case note audits of hospital admissions, covering the period from admission to six months after discharge, and audits of how stroke services were organized. Setting: Hospitals within England, Wales, Northern Ireland, the Channel Islands and the Isle of Man. Subjects: Stroke patients admitted consecutively within a three-month time frame. Main measures: Compliance with the guidelines on mood disorders and cognitive impairments, and changes between audits. Results: The 2001-2002 audit provided data on 60% of possible participants, from 145 hospitals and 5152 patients. Compliance with the guideline to screen for mood disturbance was poor; the median patient compliance rate of hospitals was 50%. More hospitals (88%) had a locally agreed cognitive assessment protocol in 2001-2002 than in 1998 (68%) and in 1999 (82%). However, actual rates of screening for cognitive difficulties were lower than implied by the existence of a local protocol. There were no strong case-mix associates of mood and cognitive screening. Access to clinical psychologists was poor. Mood and cognitive assessment rates were not much better for stroke units with access to clinical psychologists than for units without access (mood: p = 0.6, cognition: p = 0.09). Conclusions: Although compliance with some of the guidelines has improved, many areas in current psychological services for stroke urgently need attention.